ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Duha, Rustiani (Universitas Nias Raya, 2024)
This research aims to determine the obstacles to students' mathematical problem solving abilities at SMP Negeri 2 Telukdalam. This type of research approach is descriptive research. The methods used in collecting data in this research were tests and interviews. The conclusion from the research that has been carried out can be concluded that students in the high and medium ability categories in mathematics problem solving material have the ability to understand problems well. All indicators are met, namely: (1) understanding the problem, (2) developing a strategy or resolution plan (3) resolving the problem according to the plan that has been made and checking the answers again. Meanwhile, students in the low ability category in the mathematical problem solving system material have low mathematical problem solving abilities. Only 1 indicator is fulfilled, namely the indicator of solving the problem according to the plan that has been made and checking the answers again. And the other two indicators were not met because students did not understand the questions before the work was carried out.